A new species of the genus Lygosoma Hardwicke & Gray, 1827 (Squamata: Scincidae) from northeastern Cambodia, with an updated identification key to the genus Lygosoma in mainland Southeast Asia - Geissler, Peter; Hartmann, Timo; Neang, Thy (Zootaxa, 2012)
We describe a new species of the genus Lygosoma from northeastern Cambodia based on a single voucher specimen col-lected from Veun Sai Proposed Protected Forest, Veun Sai District, Ratanakiri Province. Lygosoma veunsaiensis sp. nov.is differentiated from all congeners occurring in mainland Southeast Asia by the combination of the following characters:outer ear opening absent; supranasals distinct and separated from each other by frontonasal; supranasals not fused withnasals; midbody scales in 22 rows; fontoparietals paired; five supralabials; a light stripe present on outer edge of the dor-sum; and a dark dorsolateral stripe present, from behind the eye to the tail. A key to the Southeast Asian mainland species of Lygoma is provided.